Analysis of credit card demand of UPV Faculty members - Bene, Evanhoe Candido
This research is an economic analysis of the demand for credit cards of UPV faculty members. Specifically, the research was undertaken to: describe the social and economic characteristics of existing and potential credit cardholders; estimate the credit card demand of UPV faculty and determine the significant factors affecting the demand. Logistic regression was utilized since the research is composed of a binary dependent variable which is the willingness to acquire a credit card. Results of the study revealed that 40 percent of the sampled UPV faculty members were instructors who belong to age bracket 21-28 years old. In general, the average age of a UPV faculty was 38 years old with average annual personal gross income of PhP230,000. On the other hand, 18 percent of the respondents were willing to acquire a credit card while 19 percent were credit cardholders. Deferred payment was the most common feature being used by existing cardholders while travelling was the most frequent activity in which credit card was commonly used. On the average, an existing cardholder used his/her card twice a month with an average of PhP3,530 amount of credit availed during the month and paid an average monthly finance charge of 3.25 percent. SAS output showed; That merchant acceptability, convenience and income were the significant factors affecting the demand.